The multifaceted role of phosphodiesterase 4 in tumor: from tumorigenesis to immunotherapy - Ren, Huili-li; Zhang, Shao-hui; Li, Pei-yuan (Frontiers in Immunology, 2025)
Phosphodiesterase 4 (PDE4) is an enzyme that specifically hydrolyzes the second messenger cAMP and has a critical role in the regulation of a variety of cellular functions. In recent years, PDE4 has attracted great interest in cancer research, and its role in tumorigenesis and development has been gradually elucidated. Research indicates that abnormal expression or heightened activity of PDE4 is associated with the initiation and progression of multiple cancers, including lung, colorectal, and hematological cancers, by facilitating cell proliferation, migration, invasion, and anti-apoptosis. Moreover, PDE4 also influences the tumor immune microenvironment, significantly immune evasion by suppressing anti-tumor immune responses, reducing T-cell activation, and promoting the polarization of tumor-associated macrophages toward a pro-tumorigenic phenotype. However, the PDE4 family may have both oncogenic and tumor-suppressive effects, which could depend on the specific type and grade of the tumor. PDE4 inhibitors have garnered substantial interest as potential anti-cancer therapeutics, directly inhibiting tumor cell growth and restoring immune surveillance capabilities to enhance the clearance of tumor cells. Several PDE4 inhibitors are currently under investigation with the aim of exploring their potential in cancer therapy, particularly in combination strategies with immune checkpoint inhibitors, to improve therapeutic efficacy and mitigate the side effects of conventional chemotherapy. This review provides an overview of PDE4 in tumorigenesis, drug resistance, immunotherapy, and the anti-tumor actions of its inhibitors, intending to guide the exploration of PDE4 as a new target in tumor therapy.